A novel fluorescence and DNA combination for versatile, long‐term marking of mosquitoes. Issue 6 (28th March 2021) - Faiman, Roy; Krajacich, Benjamin J.; Graber, Leland; Dao, Adama; Yaro, Alpha Seydou; Yossi, Ousmane; Sanogo, Zana Lamissa; Diallo, Moussa; Samaké, Djibril; Sylla, Daman; Coulibaly, Moribo; Kone, Salif; et al.
Abstract: Current mark–release–recapture methodologies are limited in their ability to address complex problems in vector biology, such as studying multiple groups overlapping in space and time. Additionally, limited mark retention, reduced post‐marking survival and the large effort in marking, collection and recapture all complicate effective insect tracking. We have developed and evaluated a marking method using a fluorescent dye (SmartWater ® ) combined with synthetic DNA tags to informatively and efficiently mark adult mosquitoes using an airbrush pump and nebulizer. Using a handheld UV flashlight, the fluorescent marking enabled quick and simple initial detection of recaptures in a field‐ready and non‐destructive approach that when combined with an extraction‐free PCR on individual mosquito legs provides potentially unlimited marking information. This marking, first tested in the laboratory with Anopheles gambiae s.l. mosquitoes, did not affect survival (median ages 24–28 days, p ‐adj > 0.25), oviposition (median eggs/female of 28.8, 32.5, 33.3 for water, green, red dyes, respectively, p ‐adj > 0.44) or Plasmodium competence (mean oocysts 5.56–10.6, p ‐adj > 0.95). DNA and fluorescence had 100% retention up to 3 weeks (longest time point tested) with high intensity, indicating marks would persist longer. We describe a novel, simple, no/low‐impact and long‐lasting marking method that allows separation of multiple insect subpopulations by combining unlimited length and sequence variation in the synthetic DNA tags. This method can be readily deployed in the field for marking multiple groups of mosquitoes or other insects. Résumé: Dans la biologie des vecteurs, Les méthodologies actuelles de marquage, lâcher et recapture sont limitées dans leur habilité à résoudre les problèmes complexes de la biologie des vecteurs tels que l'étude de plusieurs groupes se chevauchant dans l'espace et dans le temps. En plus, la courte durée de vie des marquages, la réduction de la longévité après marquage et les gros efforts que demande le marquage, la collecte et la recapture, compliquent davantage le suivi efficace des insectes. Nous avons développé et évalué une technique de marquage utilisant un colorant fluorescent (SmartWater®) combiné à des marqueurs d'ADN synthétiques pour marquer de manière informative et efficace des moustiques adultes à l'aide d'une pompe à air munie d'un nébuliseur. À l'aide d'une lampe de poche portable à UV, la marque fluorescente est détectée de façon rapide et simple lors des recaptures sur le terrain. Cette approche non destructive, combinée à une PCR sans extraction d'ADN sur des pattes de moustiques individuelles peut fournir potentiellement des informations illimitées sur le marquage. Ce type de marquage, testé d'abord au laboratoire avec des moustiques d' Anopheles gambiae s.l., n'a pas affecté leur survie (âge médian 24‐28 jours, p‐adj> 0.25), la ponte (médiane œufs / femelle de 28, 8, 32, 5, 33, 3 pour l'eau, colorants verts et rouges, respectivement, p‐adj> 0.44) ou leur compétence de s'infecter avec Plasmodium (oocystes moyens de 5.56 à 10.6, p‐adj> .95). L'ADN et la fluorescence avaient une rétention de 100% jusqu'à 3 semaines (le plus long moment testé) avec une intensité élevée, indiquant que les marques persisteraient plus longtemps. Nous décrivons une nouvelle méthode de marquage simple, durable avec sans/ou faible impact et durable qui permet de séparer plusieurs sous‐populations d'insectes en combinant avec une longueur illimitée et la variation de séquences dans les marqueurs d'ADN synthétiques. Cette méthode peut être facilement déployée sur le terrain pour marquer plusieurs groupes de moustiques ou d'autres insectes.